2013
DOI: 10.1089/jpm.2012.0272
|View full text |Cite
|
Sign up to set email alerts
|

Errors in Palliative Care: Kinds, Causes, and Consequences: A Pilot Survey of Experiences and Attitudes of Palliative Care Professionals

Abstract: Professionals acknowledge errors-in particular errors in communication-to be a common and relevant problem in palliative care, one that has, however, been neglected in training and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…A quarter of palliative care clinicians report medication errors occur frequently in the palliative care setting and consider them to be a leading cause of error. 17 Medication safety with opioids has been identified as a palliative care patient safety priority. [17][18][19] Despite the high volume of opioid use in this speciality, 11 and the heightened risk of exposure to and harm from opioid errors in this patient population, medication errors with opioids in palliative care services is a relatively unexplored area of patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…A quarter of palliative care clinicians report medication errors occur frequently in the palliative care setting and consider them to be a leading cause of error. 17 Medication safety with opioids has been identified as a palliative care patient safety priority. [17][18][19] Despite the high volume of opioid use in this speciality, 11 and the heightened risk of exposure to and harm from opioid errors in this patient population, medication errors with opioids in palliative care services is a relatively unexplored area of patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…13 In prior work we identified that in addition to errors from clinical interventions or medication errors (areas of attention in prior empirical work by others), errors in communication seem to play a particularly important role in palliative care. 14 We argued that for a systematic approach towards a framework of error prevention in palliative care, a shared general and comprehensive understanding of what we are actually referring to and looking for when we say ''error in palliative care'' is first and foremost important. Drawing from the same survey sample of interprofessional health care providers in palliative care, we wanted to comprehend, using a qualitative approach, what these professionals understand and describe as errors in palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that palliative care professionals need specific training on patient safety. 6 While there is a body of literature exploring patient satisfaction with hospice and palliative care, 7,8 and some literature on inpatient hospice care and the safety of various drugs in the terminally ill, there is a lack of published research that describes overall patient safety incidents in home hospice care. 4 A search of the published peer reviewed literature using the key words patient safety incidents or patient safety and hospice yielded 122 results through Medline.…”
Section: Introductionmentioning
confidence: 99%